2009
DOI: 10.1186/1479-5876-7-110
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between expression of p53, p21/WAF1, and MDM2 proteins and their prognostic significance in primary hepatocellular carcinoma

Abstract: BackgroundTumor Protein p53 (p53), cyclin-dependent kinase inhibitor 1A (p21/WAF1), and murine double minute 2 (MDM2) participate in the regulation of cell growth. Altered expression of these gene products has been found in malignant tumors and has been associated with poor prognosis. Our aim was to investigate the expression of the 3 proteins in hepatocellular carcinoma (HCC) and their prognostic significance.MethodsWe examined p53, p21/WAF1, and MDM2 expression in 181 pairs of HCC tissues and the adjacent he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
46
1
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 31 publications
7
46
1
4
Order By: Relevance
“…Following DNA damage and p53 activation, transcription of p21 is induced, which arrests cells in G 1 (21). In addition, p21 may act synergistically with proliferating cell nuclear antigen to inhibit DNA synthesis (22).…”
Section: Discussionmentioning
confidence: 99%
“…Following DNA damage and p53 activation, transcription of p21 is induced, which arrests cells in G 1 (21). In addition, p21 may act synergistically with proliferating cell nuclear antigen to inhibit DNA synthesis (22).…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry Immunohistochemistry was performed as described previously (Yun et al, 2007;Zhang et al, 2009). Briefly, after blocking, the sections were incubated with primary antibodies overnight (antip21 (Cell Signaling Technology), 1:25; anti-Ki67 (Santa Cruz Biotechnology), 1:1), followed by incubation with secondary antibodies, and further incubation with the Streptavidin-Biotin complex (Dakopatts, Glostrup, Denmark).…”
Section: Confocol Microscopymentioning
confidence: 99%
“…Thus, there is obvious biochemical evidence supporting the association between MDM2 SNP309 T/G polymorphism and liver cancer risk. Besides, MDM2 overexpression is also associated with poor survival and is a useful predictive factor for poor prognosis in patients with liver cancer (Zhang et al, 2009), which further identified the role of MDM2 in liver carcinogenesis and progression.…”
Section: Discussionmentioning
confidence: 85%